Pseudoaneurysm of mitral-aortic intervalvular fibrosa in a child: Demonstration by MDCT and MRI - Naseer A Choh; Feroze Shaheen; Hilal Rather; Khursheed Aslam (Wolters Kluwer Medknow Publications, 2013)
Subaortic left ventricular outflow tract pseudoaneurysms are rare lesions that are associated with aortic valve diseases, infective endocarditis, trauma or surgery. We present dynamic multidetector computerized tomography and cine magnetic resonance imaging features of a case of subaortic aneurysm arising from interaortic-mitral valvular region in a child with past history of infective endocarditis.